2012
DOI: 10.1371/journal.pone.0046786
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Barriers to Condom Use among Female Sex Workers in China

Abstract: BackgroundSex workers in China continue to engage in unprotected sex acts that put them at risk for contracting HIV (Human Immunodeficiency Virus) and other STIs (Sexually Transmitted Infections). The purpose of this study was to explore women’s work history, the context of sex work, condom use, HIV testing services, and potential barriers to condom use in a sample of FSWs (female sex workers) in Guangzhou, China.Methodology/Principal FindingsIn-depth, semi-structured, face-to-face interviews were conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…Past studies (Mahapatra et al, 2012;Navani-Vazirani et al, 2015) show how solicitation patterns enabled by mobile phones may be associated with high-risk sexual behaviours among sex workers indicated by lower levels of condom use. While condom use behaviours were not explored in the current study, results from the current study revealed that mobile phones facilitated closer bonds between FSWs and some clients, which may place them at risk for non-condom use with such trusted partners, an issue that has been repeatedly highlighted in past studies (Deering et al, 2011;Jie et al, 2012;Murray et al, 2007;Panchanadeswaran et al 2008Panchanadeswaran et al , 2010Voeten, Egesah, Varkevissesr, & Habberma, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Past studies (Mahapatra et al, 2012;Navani-Vazirani et al, 2015) show how solicitation patterns enabled by mobile phones may be associated with high-risk sexual behaviours among sex workers indicated by lower levels of condom use. While condom use behaviours were not explored in the current study, results from the current study revealed that mobile phones facilitated closer bonds between FSWs and some clients, which may place them at risk for non-condom use with such trusted partners, an issue that has been repeatedly highlighted in past studies (Deering et al, 2011;Jie et al, 2012;Murray et al, 2007;Panchanadeswaran et al 2008Panchanadeswaran et al , 2010Voeten, Egesah, Varkevissesr, & Habberma, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Low perceptions of risk, including trusting the partner, were the most often cited individual factors impacting condom use for both MSM 10 and female sex workers (FSW) including migrant FSW. 11 Lower condom use was associated with FSW desiring to be seen as trustworthy or build trust with clients who may become potential partners, 11,12 deciding a client "looked clean" or if regular and client partners claimed, they were uninfected. 13 Similar subjective risk reduction strategies were found in 2 studies with young clients (aged 15-24 years) of FSW in 9 hotels in Dhaka, Bangladesh, including perception of trust (inconsistent condom use with frequently visited FSW), general cleanliness (clean perceived as uninfected), perceived social status (dark skin equated with lower class and therefore fewer clients), and anal sex (perceived low risk of infection).…”
Section: Condom Usementioning
confidence: 99%
“…16 As with FSW and MSM, people who inject drugs also were found to have a low perceived sense of risk. 17,18 Structural level factors associated with condom negotiation and use in articles reviewed included economic hardship, 10,11,16 knowledge of HIV 10,19 (closely related to individual factors of risk perception and self-risk assessments), violence and trafficking, peer education and peer influence, availability of condoms and support of the brothel or entertainment venue managers, and cultural norms.…”
Section: Condom Usementioning
confidence: 99%
See 1 more Smart Citation
“…Exchange sex has previously been found to be associated with HIV infection among high-risk heterosexual men in NYC (Jenness et al, 2011). Those who sell sex may be incentivized to not use condoms (Jie et al, 2012) may have greater numbers of sex partners (Edwards et al, 2006), and may have more risky sex partners (Weber et al, 2002). Exchange sex has been found to be common among female IDUs (Astemborski et al, 1994;Davey-Rothwell and Latkin, 2008) and the majority of research concerning exchange sex has focused on females selling sex.…”
Section: Introductionmentioning
confidence: 99%